O modelo cognitivo de análise textual e a tradução - Słapek, Daniel (Neophilologica, 2011)
The aim of this article is to describe a cognitive model for text analysis proposed by E. Tabakowska, as well as its implications for translation theory and practice. The model uses the aspects of conventional imagery in cognitive grammar (perspective, prominence, ground, iconicity, etc.) to evaluate the fit between a translation with the original text. The author tries to illustrate the importance of scene construal in translation practice by analyzing a Portuguese translation of one of the W. Szymborska’s works Terrorysta, on patrzy. This presentation of a cognitive approach to translation theory is complete with a brief sketch of the main assumptions of K. Hejwowsky’s cognitive communicative theory of translation. A secondary aim is to promote the Polish school of translation studies.